Loss of consciousness in a helicopter pilot as plausible first sign of insulinoma: a case report - Pratò, Simone; Didonna, Vittoria; Garletti, Francesca; Marfia, Giovanni; Barbaresi, Adriano; Palumbo, Fabrizio; Garzia, Emanuele; Ciniglio Appiani, Giuseppe; Riboldi, Luciano; Vigna, Luisella (La Medicina del Lavoro, 2022)
A 50-year-old man who worked as a helicopter rescue pilot transiently lost consciousness while piloting a helicopter rescue. In the diagnostic process, all tests for the main possible differential diagnoses of loss of consciousness (cardiological and neurological) were performed and yielded normal results. Blood chemistry tests revealed recurrent fasting hypoglycemia and Chromogranin A was at the upper limit of normal. Fine needle aspiration guided by endoscopic ultrasonography was used to diagnose insulinoma-type neuroendocrine tumor of the pancreas. According to the Italian policies, the occupational physician aims to maintain professional skills without neglecting flight safety. A careful analysis of the relationship between the characteristics of the state of health of the aviator and his specific work needs was carried out, and he was given the opportunity to continue working as a rescue pilot thanks to medical therapies associated with organizational interventions in the workplace.